Functional and genomic characterization of three novel cell lines derived from a metastatic gallbladder cancer tumor - García, Patricia; Bizama, Carolina; Rosa, Lorena; Espinoza, Jaime A.; Weber, Helga; Cerda-Infante, Javier; Sanchez, Marianela; Montecinos, Viviana P.; Lorenzo Bermejo, Justo; Boekstegers, Felix; Davila-Lopez, Marcela; Alfaro, Francisca; et al. (Biological research, 2020)
Background Gallbladder cancer (GBC) is the most common tumor of the biliary tract. The incidence of GBC shows a large geographic variability, being particularly frequent in Native American populations. In Chile, GBC represents the second cause of cancer-related death among women. We describe here the establishment of three novel cell lines derived from the ascitic fluid of a Chilean GBC patient, who presented 46% European, 36% Mapuche, 12% Aymara and 6% African ancestry. Results After immunocytochemical staining of the primary cell culture, we isolated and comprehensively characterized three independent clones (PUC-GBC1, PUC-GBC2 and PUC-GBC3) by short tandem repeat DNA profiling and RNA sequencing as well as karyotype, doubling time, chemosensitivity, in vitro migration capability and in vivo tumorigenicity assay. Primary culture cells showed high expression of CK7, CK19, CA 19-9, MUC1 and MUC16, and negative expression of mesothelial markers. The three isolated clones displayed an epithelial phenotype and an abnormal structure and number of chromosomes. RNA sequencing confirmed the increased expression of cytokeratin and mucin genes, and also of TP53 and ERBB2 with some differences among the three cells lines, and revealed a novel exonic mutation in NF1. The PUC-GBC3 clone was the most aggressive according to histopathological features and the tumorigenic capacity in NSG mice. Conclusions The first cell lines established from a Chilean GBC patient represent a new model for studying GBC in patients of Native American descent.
Gesehen am 02.07.2020